Growth Implications of Structure and Size of Public Sectors - Hans Pitlik; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2011)
The relationship between government size and growth has received an enormous attention in the economics literature, and the recent financial crisis has forced this topic back on the agenda. A highly controversial debate in this respect is whether large governments are harmful for growth. Endogenous growth theory provides us with the view that tax structure and the composition of public expenditure may be important for growth, perhaps even more than total tax or expenditure levels. Government size and structure are, however, also reflected in the level and structure of market regulations, which may substitute or complement fiscal intervention. The study provides an overview of the growth-friendliness of fiscal and regulatory structures in a cross-section of EU 15 and EU 12 countries and highly developed OECD countries. Peripheral European (transition) countries are also included, whenever respective data are available. Our analysis is based on several measures capturing the expenditure and the tax side of the budgets, as well as regulatory policies. It is shown that the size and the structure of fiscal and regulatory regimes and, hence, the expected long-run growth impact of government activities, still differ markedly across countries.
Keywords: 330; Öffentlicher Sektor; Wirtschaftswachstum; Systemvergleich; EU-Staaten; OECD-Staaten